Phyla- and Subtype-Selectivity of CgNa, a Na+ Channel Toxin from the Venom of the Giant Caribbean Sea Anemone Condylactis Gigantea - Billen, Bert; Debaveye, Sarah; Béress, Lászlo; Garateix, Anoland; Tytgat, Jan (Frontiers in Pharmacology, 2010)
Because of their prominent role in electro-excitability, voltage-gated sodium (NaV) channels have become the foremost important target of animal toxins. These toxins have developed the ability to discriminate between closely related NaV subtypes, making them powerful tools to study NaV channel function and structure. CgNa is a 47-amino acid residue type I toxin isolated from the venom of the giant Caribbean sea anemone Condylactis gigantea. Previous studies showed that this toxin slows the fast inactivation of TTX-sensitive voltage-gated sodium (NaV) currents in rat dorsal root ganglion neurons. To illuminate the underlying NaV subtype-selectivity pattern, we have assayed the effects of CgNa on a broad range of mammalian isoforms (NaV1.2–NaV1.8) expressed in Xenopus oocytes. This study demonstrates that CgNa selectively slows the fast inactivation of rNaV1.3/β1, mNaV1.6/β1 and, to a lesser extent, hNaV1.5/β1, while the other mammalian isoforms remain unaffected. Importantly, CgNa was also examined on the insect sodium channel DmNaV1/tipE, revealing a clear phyla-selectivity in the efficacious actions of the toxin. CgNa strongly inhibits the inactivation of the insect NaV channel, resulting in a dramatic increase in peak current amplitude and complete removal of fast and steady-state inactivation. Together with the previously determined solution structure, the subtype-selective effects revealed in this study make of CgNa an interesting pharmacological probe to investigate the functional role of specific NaV channel subtypes. Moreover, further structural studies could provide important information on the molecular mechanism of NaV channel inactivation.